TRANSAKSI ONLINE, MENINGKATKAN KEPERCAYAAN DAN LOYALITAS MEREK BAGI KONSUMEN DI SURABAYA - Aniek Maschudah Ilfitriah; Mohammad Nurhadi; Sumywi Rinnukti Asri (STIE Perbanas Surabaya, 2014)
This study is aimed to determine the influence of transactional factors toward online brand trust and online brand loyalty. Online transactions factors consist of Information Quality, Perceptions of Risk, Reference from mouth to mouth, Online Shopping Experience and Sites Reputation. This is a survey research using questionnaires by Likert scale to measure all the constructs. Questionnaires distributed to the students of 14 campus locations in Surabaya. Questionnaires were distributed to 120 people and there are 5 people who do not qualify and excluded out from data so there left only 115 persons. The data were analyzed by means of Structural Equation Modelling (SEM) for testing the hypotheses. It shows that the quality of information has significant effect on online brand trust by 0.301 (p = 0.005); Perceptions of Risk has a direct and significant effect on online brand trust by 0.472 (p = 0.003), and Online Brand Trust has direct and significant effect on Online Brand Loyalty of 0.430 (p = 0.000).